Penjualan Akun Premium Disney+ Hotstar Berbasis Sharing Account Secara Tanpa Hak Melalui Marketplace Shopee - Sarif, Asri; Putri, Riska Ayu (Lembaga Penelitian Pengabdian Masyarakat dan Pusat Kajian - Universitas Ngurah Rai, 2024)
there were many business actors without the right to sell Disney+ Hotstar premium account services using a sharing account system. One of them is carried out by the online shop